A Portrait of Government Policies in Addressing Unemployment among the Young Generation in Indonesia - Arsy Adhiem, Alfido Fiqri (Proceedings of International Conference of Graduate School on Sustainability, 2026)
Since 2014, high youth unemployment has become a social phenomenon in Indonesia. In response to this challenge, the government has implemented policies to facilitate foreign investment and initiated programs such as the pre-employment card program and several scholarships for study and internships. This article aims to analyse the right to employment and a decent income for young people, and to review government programs to address this social challenge. The method used in this article is normative, with a statutory approach and a comparative analysis of the Youth Guarantee program, initiated by the European Union, to provide more comprehensive observations. The result shows that the right to employment and a decent income for young people is currently hampered by several factors, including technological disruption, skills mismatches, and the country’s economic recession due to the COVID-19 pandemic. Government-initiated programs also show the ineffectiveness of foreign investment, which has led to rising unemployment. The pre-employment card program has also proven ineffective at reducing unemployment, and scholarships benefit only a small number of young people. Based on these findings, the government is advised to revise the implementation of the pre-employment card policy and improve the sustainable investment climate to ensure continued economic growth and lower unemployment among the younger generation.